The First Zianide Minaret "minaret Of Agadir" - Khaldi Mohammed; Henni Ibtissem Meriem (My University, 2018)
The Zianid dynasty of Tlemcen (1235-1556) is known for its skill and talent in the fields of architecture and art through the various vestiges that have reached us from their monumental civilization. For that matter, the specialists did not carry out any thorough research in the decorative field and have scarcely dealt with this subject, except for the orientalist, Alfred Bel, author of an article entitled "Excavations made on the site of the Old Mosque of Agadir (Tlemcen) 1910-1911" in the Revue Africaine, or the brothers, Marcais, Georges and William, in, The Arab Monuments of Tlemcen (1903), and finally, Rachid Bourouiba with two books, Muslim Religious Art in Algeria (1973), and Contributions of Algeria to Arab-Islamic Religious Architecture (1986). This is the reason why the object of our research lies in the determination of the aesthetic principles of Zianid art, with, for example, one of its oldest minarets, that of Agadir, considered as the beginning of their architectural decorative art. By contributing to the writing of a small part of the history of their culture, our intention was to preserve the tracks this brilliant civilization.
Keywords: Zianides, Tlemcen, minaret, art, architecture, decor